2020
DOI: 10.1158/1078-0432.ccr-19-2158
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells Are Associated with Recurrent Disease in Patients with Early-Stage Non–Small Cell Lung Cancer Treated with Stereotactic Body Radiotherapy

Abstract: Purpose: Although stereotactic body radiotherapy (SBRT) is effective in early-stage non-small cell lung cancer (NSCLC), approximately 10%-15% of patients will fail regionally and 20%-25% distantly. We evaluate a novel circulating tumor cell (CTC) assay as a prognostic marker for increased risk of recurrence following SBRT.Experimental Design: Ninety-two subjects (median age, 71 years) with T1a (64%), T1b (23%), or T2a (13%) stage I NSCLC treated with SBRT were prospectively enrolled. CTCs were enumerated by ut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…Similar to Krebs et al, in our study, the presence and the number of CTC were influenced by previous lines of therapy. Indeed, patients with a positive history for previous therapy had a mean number of CTC lower than those who underwent ICI as first-line therapy (p = 0.004) [7]. As a consequence, the presence of CTC in the peripheral blood after chemotherapy might suggest the grade of response to treatment or, in other words, the aggressiveness of the tumor determining how fast cancer can return after a macroscopic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Krebs et al, in our study, the presence and the number of CTC were influenced by previous lines of therapy. Indeed, patients with a positive history for previous therapy had a mean number of CTC lower than those who underwent ICI as first-line therapy (p = 0.004) [7]. As a consequence, the presence of CTC in the peripheral blood after chemotherapy might suggest the grade of response to treatment or, in other words, the aggressiveness of the tumor determining how fast cancer can return after a macroscopic response.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that CTC enumeration is related to poor prognosis in different metastatic malignancies, including lung, breast, colorectal, prostate, and gastric cancer. Furthermore, molecular characterization of CTC might expand our knowledge on tumor heterogeneity, especially in patients for whom tissue biopsies are difficult to perform [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For lung cancer, one study shows that the pre-chemoradiation CTCs is negatively associated with PR in advanced NSCLC patients [22]. Furthermore, a study displays that elevated pre-radiation CTCs and persistence of CTCs post-radiation are associated with higher recurrence risk outside the targeted treatment site in early stage NSCLC patients [26]. Another study displays that higher pre-chemoradiation CTCs level is an independent predictive factor for worse OS in small cell lung cancer patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…(19) CTCs are easily accessible through a simple blood draw, amenable to serial sampling, and recognized as a potential alternative to invasive, technically challenging tissue biopsies. (20) Although the prognostic significance of CTCs is established in several malignancies, (21,22) data for their utility in HCC remain limited. (23) More recently, subset characterizations of CTCs expressing various phenotypic profiles such as epithelial-to-mesenchymal transition markers (24,25) and stem cell markers (26) have been shown to have significant prognostic utility.…”
mentioning
confidence: 99%